Risk factors for mycobacterium tuberculosis infection among HIV/AIDS populations in China - Zhao Junpeng; Richard Avoi; Azman Atil Azmi; Zheng Baiqin; Wang Lei; Qiang Rundong; Cao Huihui; Gao Weilin; Zhang Xu; Du Ruihuan; Yao Yuhong; Qi Wenjie; et al. (Eman Research Publishing, 2024)
Background: HIV/TB coinfection remains a significant concern, particularly in high-risk populations. In China, the HIV/AIDS population is at a heightened risk for TB, with those infected showing a 20-37 times higher likelihood of developing TB. This study aims to explore factors contributing to Mycobacterium tuberculosis (MTB) infection within the HIV/AIDS population in Hebei Province, China, a region with a notable TB burden despite its moderate HIV prevalence. Method: A retrospective cohort study was conducted using data from the Infectious Disease Monitoring System of the China Center for Disease Control and Prevention (IDMS CDC). Data were collected from HIV/AIDS patients in high-risk counties of Hebei Province, focusing on demographic, clinical, and transmission-related factors. A total of 608 HIV/AIDS patients were included, with 504 completing the cohort study. The analysis employed Cox proportional hazards regression to assess the relationship between transmission routes, CD4+ T lymphocyte counts, and MTB infection. Results: Among the 504 participants, 54 developed TB, with significant correlations found between transmission routes and initial CD4+ T lymphocyte counts. HIV patients with a same-sex transmission route were 4.77 times more likely to develop TB compared to those with blood-borne transmission. Furthermore, individuals with an initial CD4+ count of 0–350/μl had nearly three times the risk of TB infection compared to those with higher counts. These findings highlight the critical role of immune status and transmission routes in determining TB infection risk. Conclusion: This study underscores the importance of CD4+ T lymphocyte counts and transmission routes as key predictors of TB risk in HIV-positive individuals. Tailored interventions, including targeted TB screening for MSM populations and those with lower CD4+ counts, are crucial for improving TB prevention and control.